KOMUNIKASI TEOLOGI ADAT DAN SYARI’AT ISLAM DALAM WILAYATUL HISBAH DI ACEH - Ridwan Muhammad Hasan (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2019)
Nanggroe Aceh Darussalam (NAD) was one of the areas that the first time that Applied in the form of syari’at Islam that was based on the Regulation area (Regional Regulations) No. 5 in 2000 and No. Regional Regulations 33 in 2001 or that more was known in the Acehinese community with the Qanun term. In the Acehinese community of Syari’at Islam also was one of the solutions to be able to complete all the happened in the community, because with syari’at Islam also could resolve all the problems. Islamic law was the synonym from ad-din that is Allah's teaching whole that was brought by the Prophet Muhammad SAW, that covered in belief fields, the moral and laws to be able to give the concept of peacefulness that was real without the limit that must have been based by various the elastic law as well as touched to various dimensions and the aspect of pure theologyKeywords: Communication, Theology,Custom and Islamic Law.